Chapter 6 Thomist Classical Theism Divine Simplicity within Aquinas' Triplex Via Theology - De Haan, Daniel (Taylor & Francis, 2023)
Defenders and critics of divine simplicity rightly look to Thomas Aquinas's important contributions to this pillar of classical theism (=CT). But few contemporary discussions notice the way Aquinas employs pseudo-Dionysius's triplex via as a principled heuristic that governs and organizes his theological enquiries concerning divine simplicity. This oversight has led to misinterpretations of Aquinas's doctrine of divine simplicity (=DDS), which must be situated within his triplex via theology (=TVT). In this chapter I show that, like Aquinas's DDS, the value of Thomist TVT extends beyond historical exegesis and provides exponents of CT with a fertile alternative to the more well-known Anselmian inspired heuristic of perfect being theology (=PBT). In the first part I introduce two problems for CT that cannot be resolved by PBT and Thomistic accounts of DDS that omit Aquinas's TVT. In the second part, I explain what Thomistic TVT is and why its integrated threefold way of understanding God via causality, negation, and super-eminence can overcome these problems for CT.